Gene regulation and genetic susceptibility to neoplastic transformation: AP-1 and p80 expression in JB6 cells. - Bernstein, L R (1991)
The mouse epidermal JB6 cell system consists of clonal genetic variants that are sensitive (P+) or resistant (P-) to the promotion of neoplastic transformation by phorbol esters and other tumor-promoting agents. P+ cells display AP-1-dependent phorbol-ester-inducible transactivation of gene expression, whereas P- cells have a defect in transactivation. Transfection of promotion sensitivity gene pro-1 into P- cells reconstituted both P+ phenotype and AP-1-dependent phorbol-ester-inducible transactivation. P- and P+ cells exhibited induction of c-jun and c-fos messenger RNA levels by phorbol ester, but P- cells had significantly lower basal and induced levels of jun mRNA than P+ cells. Basal and induced levels of c-jun protein were significantly lower in P- cells as well. Differences in levels the 80-kDa pI 4.5 protein p80 were also observed in JB6 cells as a function of preneoplastic progression; high levels of p80 protein and mRNA were observed in P- cells, intermediate levels in P+ cells, and negligible levels were observed in transformed derivatives of JB6 cells. Phorbol ester treatment induced phosphorylation but not synthesis of p80. These data are consistent with the hypotheses that AP-1 is required in the signal transduction pathway for promotion of neoplastic transformation by tumor promoter, that pro genes may control AP-1 activity, that threshold levels of Jun mRNA and protein may play a role in transactivation and promotion sensitivity, and that the p80 protein in JB6 cells may behave in vivo as a suppressor of cellular transformation.